ENGINEERING DEVELOPMENT OF PASSIVE IONOSONDE TO STUDY THE EFFECT OF THE BLACKOUT ON HF COMMUNICATION - Belgibaev, Ruslan; Ivanov, Dmitriy; Ivanov, Vladimir; Ryabova, Natalya; Ryabova, Maria (Journal of Applied Engineering Science, 2016)
The development of passive ionosonde that enables to assess the information of technological characteristics of ionospheric radio channel in real time, was carried, which is part of the long distance HF communications systems. On its basis there was conducted applied research of the effect of radio blackout of HF communications caused by the X-ray flare on the sun on the frequency capacity of the multi-dimensional ionospheric radio. It was found out that the blackout of R2 category leads to the cessation of HF communication about 2600 telephone channels, i.e. frequency channel capacity is reduced by 34%. It was set that the relaxation time of blackout is in 1.7 times more than the relaxation time of the X-ray flash.